Suggestions on how to use bibliographic references for dealing with curricular strategies. History of Cuba II. Dentistry - Rosa Elena Tennyson Cantillo; Andrea Margarita Hernández Salgado; Sol Ángel Rosales Reyes; Magalys Clark Silot; Mauricio González Ruiz; Mahely Olivera Valdés (Universidad de Ciencias Médicas de La Habana, 2018)
Introduction: The History of Cuba II syllabus lacks suggestions about bibliography that allow the teaching staff to deal with the curricular strategies in the Curriculum "D" in dental studies. Objective: To suggest the use of bibliographies for the treatment of curricular strategies in the subject History of Cuba II in Dentistry. Material and methods: A descriptive pedagogical research was conducted.  Methods of document analysis, methodological workshop, and bibliographic review were used. Results:  A total of 33 bibliographies were found, and proposals were made for linking curricular strategies in each of the topics of History of Cuba II syllabus for dental studies. Conclusions: The suggested bibliographies can contribute to the treatment of curricular strategies in the subject History of Cuba II, and favor the comprehensive training of the first- year dental students. Keywords: bibliographies, curricular strategies, History of Cuba II, pedagogical research.